ANALYSIS OF DIGITAL LIBRARY SERVICE QUALITY ON USER SATISFACTION USING WEBQUAL, LIBQUAL AND IPA METHODS - Rahman, Eman; Jazman, Muhammad; Zarnelly, Zarnelly; Permana, Inggih (Informatika, Universitas Jenderal Soedirman, 2023)
Universitas Pahlawan Tuanku Tambusai has used the information system Senayan Library Management System (SLiMS) version 7. SliMS is an integrated system to provide information to support operational, management and decision-making functions in libraries. However, there are still obstacles in its use, namely, the lack of tools and technology to support the implementation of the SLiMS system, the unattractive SliMS content, the OPAC service menu is less effective in searching for references in the library, and the book collection is rarely updated so it does not meet what the user needs. This study aims to measure the service quality of SLiMS from the user's perspective. This research instrument used Web Quality (WebQual), Library Quality (LibQual), and Importance Performance Analysis (IPA) methods. The results of this study resulted in a good level of system service quality but GAP was still found from perceived performance which still had a value of <0 or -0.63 and a conformity level of 78%, which meant that there were still results of user dissatisfaction with the performance provided by the service. SLiMS Hero University of Tuanku Tambusai. Quadrant A results are a top priority to be improved. the variables are: Easy to navigate (UQ3), Attractive appearance (UQ5), Latest available information (SI1), Provides detailed information (SI4), Provides up to date information (IC3), Cleanliness and beauty (LP2), Lighting and temperature settings (LP3), Guidance from the librarian (AS5).